2022
DOI: 10.3389/fgene.2022.898204
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression of GPX8 is correlated with poor prognosis in GBM patients

Abstract: Glutathione peroxidase 8 (GPX8), located in the endoplasmic reticulum, is associated with poor prognosis in several cancers. However, the expression and functions of GPX8 in cancers remain unclear. The purpose of this study was to explore the expression and functions of GPX8 in glioblastoma (GBM). We obtained expression data of GPX8 by accessing the TCGA, CGGA, GEPIA, and TIMER2.0 databases and validated them using western blot and immunohistochemistry. The Kaplan–Meier overall survival curve and Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(56 reference statements)
1
6
0
1
Order By: Relevance
“…The PMT occurs in gliomas, similar to the EMT process, and is considered to be an important mechanism for promoting metastatic 35 , 47 , 48 . The results of our study confirm that ALKBH5 contributes to formation of the MES phenotype and promotes PMT in GBM, which is consistent with the previous study that ALKBH5 can affect the malignant progression of GBM 49 . In addition, we verified that proline synthesis promoted proliferation and PMT in GBM cells.…”
Section: Discussionsupporting
confidence: 93%
“…The PMT occurs in gliomas, similar to the EMT process, and is considered to be an important mechanism for promoting metastatic 35 , 47 , 48 . The results of our study confirm that ALKBH5 contributes to formation of the MES phenotype and promotes PMT in GBM, which is consistent with the previous study that ALKBH5 can affect the malignant progression of GBM 49 . In addition, we verified that proline synthesis promoted proliferation and PMT in GBM cells.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, EMP3, RGS16, PLAU, TAGLN2, STEAP3, CDHR1, OSMR, SERPINH1, PDPN, CHI3L1, ABCC3, SERPINE1, SOCS1, GPX8, GPNMB, CLEC5A, FOSL2, ICAM1, PRF1 and ITPRIP serve as prognostic markers for gliomas. 9 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Among them, RGS16, CLEC5A and TAGLN2 are key regulatory factors that promote glioma progression by activating the PI3K‐AKT pathway in gliomas. 53 , 54 , 55 , 56 Additionally, upregulated STEAP3 in gliomas facilitates tumour cell migration and invasion and is significantly associated with immune‐infiltrating cells, including macrophages and neutrophils, particularly M2 macrophages.…”
Section: Discussionunclassified
“…Many of these genes have demonstrated associations with the prognosis or progression of gliomas. Notably, EMP3, RGS16, PLAU, TAGLN2, STEAP3, CDHR1, OSMR, SERPINH1, PDPN, CHI3L1, ABCC3, SERPINE1, SOCS1, GPX8, GPNMB, CLEC5A, FOSL2, ICAM1, PRF1 and ITPRIP serve as prognostic markers for gliomas 9,41–52 . Among them, RGS16, CLEC5A and TAGLN2 are key regulatory factors that promote glioma progression by activating the PI3K‐AKT pathway in gliomas 53–56 .…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of GPX8 is associated with MES features and is negatively correlated with anterior PN features, thus suggesting that GPX8 may promote PMT in GBM. Correlation analysis has shown that GPX8 expression modulation is associated with the IL1-MYD88-IRAK-NF-κB pathway and immune infiltration in GBM 110 . Furthermore, the TGF-β-induced CLDN4/TNF-α/NF-κB signaling axis plays a key role in EMT in gliomas 111 .…”
Section: Mesenchymal Transition Regulators Of Gbmmentioning
confidence: 99%